SERVICE INNOVATION OF VEHICLE TAX IN IMPROVING QUALITY OF PUBLIC SERVICE TO SAMSAT OFFICE OF PANDEGLANG REGENCY - Diki Defrian; Ahmad Sururi; Budi Hasanah (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2021)
The complexity of problems such as piling up queues, illegal fees, the practice of brokers and the lack of willingness and awareness of the public in paying motor vehicle taxes are some of the problems that must be faced by the UPT Samsat Pandeglang Regency. The purpose of this study was to discuss the innovation of motor vehicle tax services in improving the quality of public services in Samsat, Pandeglang Regency. This research method uses a descriptive type with a qualitative approach. The data collection techniques in the form of observation, interviews and documentation as well as data analysis techniques include reduction, verification and conclusion. The results of the study indicate that the implementation of the motor vehicle tax service innovation in Samsat, Pandeglang Regency, has been running well, although it is still necessary to continue to encourage more intensive service innovations on indicators of suitability and complexity. Keywords: Innovation, Public Service, Vehicle Tax, Pandeglang.